European Victory - D'Arcy-Dawson, John (London MacDonald & Co. Publishers Ltd.)
Many of the earliest books, particularly those dating back to the 1900s and before, are now extremely scarce and increasingly expensive. We are republishing these classic works in affordable, high quality, modern editions, using the original text and artwork.
Include Illustrations.
John D'Arcy-Dawson, War correspondent with the British and American Forces.
Keywords: World War (1939-1945) -- Military campaigns -- Western Front (World War (1939-1945)) -- Allied Forces